Money, wealth, and economic theory - Pesek, Boris P.; Saving, Thomas Robert (New York : Macmillan, 1967)
The book examines various economic theories on wealth and money as well as financial intermediaries- production of money, debt on wealth and an accounting interpretation of money. It also macro economic analysis and various macroeconomic model.
includes index
Bibliography: p. 426-432.
usc 29/06/2017
Loans
Keywords: Money; Wealth